Surgical revision of radial head fractures: a multicenter retrospective analysis of 466 cases - Hackl, Michael; Wegmann, Kilian; Hollinger, Boris; El-Zayat, Bilal F.; Seybold, Dominik; Gühring, Thorsten; Schnetzke, Marc; Schmidt-Horlohé, Kay; Greiner, Stefan; Lill, Helmut; Ellwein, Alexander; Glanzmann, Michael C.; et al. (Journal of shoulder and elbow surgery, 2019)
Background - Radial head fractures lead to persisting disability in a considerable number of cases. This study aimed to investigate their most common revision causes and procedures. - Methods - This multicenter retrospective study reviewed the cases of 466 adult patients who had undergone surgical revision after operative or nonoperative treatment of a radial head fracture. The initial diagnosis was a Mason type I fracture in 13.0%, Mason type II fracture in 14.6%, Mason type III fracture in 22.8%, Mason type IV fracture in 20.9%, terrible-triad injury in 12.8%, Monteggia-like lesion in 13.1%, and Essex-Lopresti lesion in 2.0%. Initial treatment was nonoperative in 30.2%, open reduction and internal fixation (ORIF) in 44.9%, radial head arthroplasty in 16.6%, radial head resection in 3.7%, sole treatment of concomitant injuries in 2.6%, and fragment excision in 2.0%. Up to 3 revision causes and procedures were recorded per case. - Results - The most common complications were stiffness (67.4%), instability (36.5%), painful osteoarthritis (29.2%), ORIF related (14.8%), nonunion or necrosis (9.2%), radial head arthroplasty related (7.5%), ulnar neuropathy (6.0%), and infection (2.6%). Revision procedures frequently included arthrolysis (42.1%), arthroplasty (24.9%), implant removal (23.6%), ligament repair or reconstruction (23.0%), débridement (14.2%), repeated ORIF (8.2%), and/or radial head resection (7.7%). Mason type I or II fractures were primarily revised because of stiffness and painful osteoarthritis. Complications after Mason type III fractures were predominantly ORIF related. Fracture-dislocations showed a wide range of complications, with instability and stiffness comprising the most common causes of revision. - Conclusions - The complications of radial head fractures are characteristic to their classification. Knowledge of these findings might guide surgeons in treating these injuries and may help counsel patients accordingly.
Gesehen am 30.01.2020